Molecular genetic analysis of PKHD1 by next-generation sequencing in Czech families with autosomal recessive polycystic kidney disease. Issue 1 (December 2015) - Obeidova, Lena; Seeman, Tomas; Elisakova, Veronika; Reiterova, Jana; Puchmajerova, Alena; Stekrova, Jitka
Abstract Background Autosomal recessive polycystic kidney disease (ARPKD) is an early-onset form of polycystic kidney disease that often leads to devastating outcomes for patients. ARPKD is caused by mutations in thePKHD1 gene, an extensive gene that encodes for the ciliary protein fibrocystin/polyductin. Next-generation sequencing is presently the best option for molecular diagnosis of ARPKD. Our aim was to set up the first study of ARPKD patients from the Czech Republic, to determine the composition of their mutations and genotype-phenotype correlations, along with establishment of next-generation sequencing of thePKHD1 gene that could be used for the diagnosis of ARPKD patients. Methods Mutational analysis of thePKHD1 gene was performed in 24 families using the amplicon-based next-generation sequencing (NGS) technique. In patients without 2 causal mutations identified by NGS, subsequent MLPA analysis of thePKHD1 gene was carried out. Results Two underlying mutations were detected in 54 % of families (n = 13), one mutation in 13 % of families (n = 3), and in 33 % of families (n = 8) no mutation could be detected. Overall, seventeen different mutations (5 novel) were detected, including deletion of one exon. The detection rate in our study reached 60 % in the entire cohort of patients; but 90 % in the group of patients who fulfilled all clinical criteria of ARPKD, and 42 % in the group of patients with unknown kidney pathology. The most frequent mutation was T36M, accounting for nearly 21 % of all identified mutations. Conclusions Next-generation sequencing of thePKHD1 gene is a very useful method of molecular diagnosis in patients with a full clinical picture of ARPKD, and it has a high detection rate. Furthermore, its relatively low costs and rapidity allow the molecular genetic analysis of patients without the full clinical criteria of ARPKD, who might also have mutations in thePKHD1 gene.